Inovasi Promosi Desa Melalui Vidio Dokumenter: Meningkatkan Kesadaran Pengelolaan Sampah di Padangsambian Klod - Komang Widhya Sedana Putra P; Mahadhika Feryo Gotama; Kadek Wulandari Laksmi P; IGN Oka Ariwangsa (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Waste management remains a critical issue in Indonesia, with waste generation reaching 26.1 million tons in 2024. Low public awareness exacerbates this problem, as 72% of Indonesians still lack concern for proper waste disposal. Community-based waste management, such as waste banks, has emerged as an effective solution to encourage waste sorting and recycling. Objective: This community service program aims to increase public awareness and participation in sustainable waste management through an educational documentary video. The documentary highlights the waste bank initiative in Padangsambian Klod Village, demonstrating its economic and environmental benefits. Method: A qualitative descriptive approach with a participatory method was employed. Data collection involved direct observation, in-depth interviews with key stakeholders, and documentation through video recording. The video was then edited and disseminated via social media to reach a broader audience. Result: The documentary successfully raised public awareness about proper waste management, as evidenced by increased participation in the village’s waste bank program. The video effectively conveyed educational messages, leading to higher waste sorting rates and greater engagement from the community. Social media dissemination expanded the program's reach, attracting attention from local authorities and other communities. Conclusion: The use of documentary videos as an educational tool proved effective in promoting sustainable waste management. This approach can be replicated in other communities to enhance public awareness and participation. Continuous evaluation and collaboration with stakeholders are recommended to ensure long-term impact.